EVALUASI SISTEM DRAINASE DALAM UPAYA PENANGGULANGAN BANJIR (STUDI KASUS KELURAHAN HONIPOPU KOTA AMBON) - Ibrahim, Nilam Ismi; Berhitu, Petrick Th.; Puturuhu, Ferad (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2022)
Urban drainage systems serve to remove excess water in cities. The excess water can be in the form of rainwater, domestic wastewater and industrial wastewater. In order to prevent flooding in urban areas, the urban drainage system must be integrated with sanitation, garbage, city flood control and also the condition of the surrounding environment. The aims of this study were 1) to identify the drainage system that causes flood inundation in the research area 2) to determine the appropriate direction for the drainage system in an effort to prevent flooding in the study area. Data collection methods used in this study include: observation, interview techniques, agency surveys, and documentation. Analysis of the data used is an analysis of the basic physical conditions of the study area, including slope, hydrology, rainfall conditions and land use. Poor drainage conditions in Honipopu Village are caused by very high sedimentation and waste water discharge, causing drainage to siltation. The direction of the drainage system in an effort to deal with flooding in the Honipopu village is the strategy of rehabilitation and normalization of drainage. Keywords: Evaluation Drainage system, Flood Management, Kelurahan Honipopu